Bereaved caregivers' satisfaction with end-of-life care. (4th July 2022) - Frame, Abbey; Grant, Janie Busby; Layard, Elizabeth; Scholz, Brett; Law, Eleanor; Ranse, Kristen; Mitchell, Imogen; Chapman, Michael
Abstract : End-of-life care involves treatment and support offered to terminally ill individuals and their caregivers. Effective communication and decision-making, illness and symptom management, relationship with doctors, characteristics of the health care team, and the involvement and needs of caregivers have all been proposed to contribute to the quality of the end-of-life experience. This study sought to establish bereaved caregivers' experiences of the quality of the elements of end-of-life care delivered to their loved ones. Bereaved caregivers who had lost a loved one who was cared for in an acute care University-affiliated hospital, with 670 beds, located in the Australian Capital Territory during the previous 6−12 months ( N =91), were surveyed using a modified version of the Canadian Health Care Evaluation Project questionnaire. The findings indicated that the bereaved caregivers were generally very satisfied with their loved one's end-of-life care. The age of the caregiver, the preferred location of death for both patient and caregiver, if death was expected, and religious affiliation were associated with satisfaction of the end-of-life care delivered. Key areas for improvement of end-of-life care included factors related to the relationships between doctors and those receiving care, characteristics of the health care team, illness management, communication and decision-making, and the involvement of caregivers. These findings have significant implications for this hospital and those seeking to improve outcomes in end-of-life care settings more widely, by providing baseline data on caregiver-evaluated care quality and identifying high-priority areas for targeted intervention.